Geneza wyboru zasadniczego z perspektywy tradycji chrześcijańskiej - Torończak, Edward (Poznańskie Studia Teologiczne, 2008)
Theologians of the so-called new moral theology aiming to renew moral theology developed a theory of a fundamental option identifying it as the ‘new’ paradigm o f morality. They accused the moral theology’s tradition, to a certain extent rightly, of too strong an emphasis on the objective dimension of the moral action ignoring its subjective dimension on which, in their opinion, the quality of choices a person makes depends. However, reflections upon the origins of the fundamental choice from the perspective of Christian tradition demonstrated that St. Augustine, St. Thomas, St. Alphonsus Liguori in their writings pointed out the subjective dimension of morality, emphasising the importance of conscience, freedom and moral decision in the Christian life. The moral and theological reflections o f these authors contain references to a deeply personal aspect of moral activity since, in fact, a moral act ‘is bom’ deep within a person and is directed towards the ultimate aim. It is in the fundamental moral decision, understood as the life’s essential direction towards God, where a relation towards subjective not only objective dimension of the moral order is clear, since such a decision ultimately comes from the depths of the acting person’s freedom.